Histology, Histochemistry and Fine Structure of the Lacrimal and Nictitans Gland in the South American ArmadilloChaetophractus villosus (Xenarthra, Mammalia) - Aldana Marcos, Hernan Javier (2002)
The anatomical, histological, histochemical and ultrastructural characteristics of the lacrimal gland (LG) and nictitans gland (NG) of the armadillo Chaetophractus villosus were described. The histochemical and histological features of both glands in male and female adult animals were compared. The tissues were processed with conventional techniques for light and transmission electron microscopy. Fixed specimens were submitted to a battery of tests for glycans, glycosaminglycans, glycoconjugates, proteins, and lipids. The LG of the armadillo may be considered within the set ofglandulae lacrimales superior in which primates, carnivores, perisodactyls and artiodactyls are included. The localization of the NG was similar to that of other mammals. Lacrimal and NG were histologically and histochemically identical. Thesecretory endpieces consisted of three cell types: (1) Mucous cells (MC) with different types of mucous secretory granules with neutral and sialic acid-containing glycoconjugates (GCs). (2)Seromucous cells (SMC) showing a variety of moderately electron dense secretory granules with flocculent material with carboxylated acidic, neutral, and sialic acid-containing GCs. Intercellular canaliculi with junctional complexes and basolateral intercellular spaces were frequent. (3) Serous cells (SC) with electron dense secretory granules. Histochemically, they showed the strongest reaction for proteins and neutral, weakly acid and carboxylated acidic GCs. The epithelium of the intra- and inter-lobular excretory ducts showed secretory activity, junctional complexes, and wide basolateral intercellular spaces with lateral folds. The endpieces and ducts were surrounded by myoepithelial cells. The stroma was characterized by fenestrated endothelium, unmyelinated axons, and abundant plasma cells. MC, SMC, and the duct system were richly innervated by hypolemmal nerve terminals.